2018
DOI: 10.3747/co.25.3848
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to, and Outcomes of, a Galactomannan Screening Protocol in High-Risk Hematology Patients

Abstract: Background A twice-weekly galactomannan (gm) screening protocol was implemented in high-risk hematology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Our analysis revealed that the use of empirical antifungal treatment was a key driver in the cost-effectiveness of GM surveillance. Clinical studies have shown benefits of routine GM surveillance in terms of reduced cost and the prescription of antifungal treatment, but not in mortality rates [8,10,12]. This was made possible through serial GM surveillance as a trigger to guide further investigation and initiation of antifungal treatment as opposed to empirical prescription applied in prolonged neutropenic fevers unresolved by board-spectrum antibiotics [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis revealed that the use of empirical antifungal treatment was a key driver in the cost-effectiveness of GM surveillance. Clinical studies have shown benefits of routine GM surveillance in terms of reduced cost and the prescription of antifungal treatment, but not in mortality rates [8,10,12]. This was made possible through serial GM surveillance as a trigger to guide further investigation and initiation of antifungal treatment as opposed to empirical prescription applied in prolonged neutropenic fevers unresolved by board-spectrum antibiotics [13].…”
Section: Discussionmentioning
confidence: 99%
“…There was not any significant trend in survival benefits from the use of a biomarker diagnostic approach as with previous studies. Based on a cohort study of haematological patients receiving fluconazole prophylaxis, GM surveillance led to improved clinical success-defined as patients not using antifungal agents 6 weeks after the end of the episode or the day before subsequent cycles of chemotherapy [8]. The model did not include the cost of adverse events or management of the underlying malignancies because these costs were assumed to be similar in all treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delay in starting treatment is often associated with increased mortality. 5 , 6 , 7 , 8 These fungal infections present diagnostic challenges associated with traditional culture and histological examination methods. The diagnosis is based on the combination of the patient's risk factors, clinical symptoms and signs, culture, histopathological exams, and detection of antigenic components of the fungus, such as Galactomannan (GM).…”
Section: Introductionmentioning
confidence: 99%
“…GM testing is available in many hospitals, but there are still questions about the role it plays in decision-making related to antifungal treatment in high-risk IFI/IA patients. 6 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%